Formation mechanism of the solid electrolyte interphase in different ester electrolytes - Yang, Shi-Jie; Yao, Nan; Xu, Xiang-Qun; Jiang, Feng-Ni; Chen, Xiang; Liu, He; Yuan, Hong; Huang, Jia-Qi; Cheng, Xin-Bing (Journal of materials chemistry. A, Materials for energy and sustainability, 2021)
The solid electrolyte interphase (SEI) plays a critical role in determining the performance of lithium metal batteries. Herein, the formation mechanisms of the SEI is investigated in electrolytes with two frequently adopted solvents: diethyl carbonate (DEC) and ethylene carbonate (EC). The dispersity of reaction products between Li and solvents are explored by 1 H-NMR and first-principles calculations. Lithium ethylene carbonate (LEC), the reduction product of DEC, disperses in the electrolyte, while lithium ethylene dicarbonate (LEDC), the reduction product of EC, cannot disperse in the electrolyte. First-principles calculations further prove that the low polymerization degree of (LEC) n leads to its good dispersity, while poly-LEDC macromolecules can remain on the Li surface acting as the stable SEI. This work not only clearly points out the formation mechanism of SEI, but also demonstrates the functional role of EC, which can provide novel insights for electrolyte design of advanced batteries. The solid electrolyte interphase (SEI) plays a critical role in determining the performance of lithium metal batteries.